Frozen dough steamed products: Deterioration mechanism, processing technology, and improvement strategies - Zhang, Meng‐Li; Guo, Xiao‐Na; Sun, Xiao‐Hong; Zhu, Ke‐Xue (Comprehensive reviews in food science and food safety, 2024)
Fresh dough products lead to instability in product quality, high production costs, and more production time, which seriously affects the industrial production of the food industry. The frozen dough technology mitigates the problems of short shelf‐life and easy deterioration of quality during storage and transportation. It has shown a series of advantages in large‐scale industrialization, high‐quality standardization, and chain operation. However, the further development of frozen dough is restricted by the deterioration of the main components (gluten, starch, and yeast) caused by freezing. This review summarizes the main production process of frozen steamed bread and buns, and the deterioration reasons for the main component of frozen dough. The improvement mechanisms of raw ingredients, processing technology, processing equipment, and additives on frozen dough quality were analyzed from the perspective of improving gluten network integrity and yeast freeze tolerance. From prefermented frozen raw to steamed products without thawing has become the preferred production process to improve production efficiency. Wheat flour mixed with other flour can maintain the gluten network continuity of frozen dough. The freeze tolerance of yeast was improved by treatment with yeast suspension, yeast cell encapsulation, screening hybridization, and genetic engineering. Process optimization and new technology‐assisted fermentation and freezing effectively reduce freezing damage. Various additives improve the freeze resistance of the gluten‐starch matrix by promoting protein cross‐linking and inhibiting water migration. In addition, ice structural proteins and ice nucleating agents have been proven to change the growth morphology and formation temperature of ice crystals. More new technologies and additive synergies need to be further explored.